Metaphors and Methodologies: Living Beyond the Systems Machine - Kendall, Julie E.; Kendall, Kenneth E. (MIS Quarterly, 1993)
Metaphors are the cognitive lenses we use to make sense of all situations. Intimately interconnected with the way we think, metaphors are fundamental in shaping reality. Building on work about metaphors in organizational life, this paper examines the language of information systems users in 16 different organizations. The results confirm the existence of six main metaphors (journey, war, game, organism, society, and machine) and adds three metaphors that also emerged from the language of IS users (family, zoo, and jungle). Dramatistic analysis was used to reveal that seven of these principal metaphors are found in commonly used systems development methodologies. For example, the systems development life cycle draws upon the “game” metaphor, and structured methodologies and CASE tools are akin to the “machine” metaphor. Analysts who are aware of the existence of these metaphors (both in the user organization and within the methodologies themselves) will begin to see the systems development process in an entirely different light. Caution must be undertaken, however, when using this approach. First, analysts should lead the systems development process by selecting a methodology to match user metaphors, not the other way around. Seccond, analysts must see, rather than suppress, the paradoxical richness of metaphors. Third, analysts should not limit the number of metaphors because it limits the usefulness of this approach. Fourth, analysts should be adequately trained in a variety of systems development methodologies. Finally, analysts should use metaphorical analysis in conjunction with other approaches. Using the recommendations and findings for guidance, analysts can begin to develop the power of metaphorical analysis to better understand and communicate with users during the development process.